“The Effect of the means of the Tourist Media in Developing the Museums in Baghdad city –on Exploratory study of a sample of workers in Al-Baghdadi Museum” - JAMAL, DINA HAMID (International Journal of Psychosocial Rehabilitation, 2020)
They differ greatly in terms of their nature and shape according to the cultural and historical framework and in order to understand the reality of living for the ancient Iraqis, so the media had to focus on them to advance the reality of museums, their development and harnessing them in the service of society, especially as they reflect the progress of the Iraqi civilization and what it holds of multiple cultural hoardings so the research was based on Two variables interact with each other to form the intellectual and philosophical framework and try to identify the influence relations between the two variables and then come up with conclusions and recommendations that contribute to increasing the influence of the media in the development of museums in Baghdad in general and the Baghdad Museum in particular.